Towards the successful integration of e‐learning systems in higher education in Iraq: A student perspective. (22nd August 2018) - Ameen, Nisreen; Willis, Robert; Abdullah, Media Noori; Shah, Mahmood
Abstract: This study aims to analyse the factors that can explain the adoption and effective use of a new e‐learning system in Iraq. To achieve this, it uses a selection of factors that are present in the technology acceptance model (TAM) and the unified theory of acceptance and use of technology (UTAUT) model, and it includes three additional factors. The study hypothesises new relationships between the selected factors. Questionnaires were distributed to 300 university students in Iraq. Partial least squares‐structural equation modelling (PLS‐SEM) was used to analyse the data received. The findings suggest that perceived usefulness (PU), perceived ease of use (PEOU), subjective norms (SNs), information quality (IQ), system quality (SQ), technical support (TS) and self‐efficacy (SE) have significant effects on behavioural intention (BI). In turn, BI and TS have significant direct effects on the actual use (AU) of e‐learning systems. The factors age, gender and experience significantly moderated some of the relationships in the model. The research has several implications for policy makers, universities and the management of e‐learning systems.